Implementing Digital Marketing Strategy to Enhance MSMEs Competence: A Case Study of Cipageran Milk Center in Cimahi - Bethani Suryawardani; Ulfah Nurwahidah; Salsabila Shabriyyah Al Syahr; Allya Nihayah; Evi Febriana (International Journal Of Community Service, 2026)
Cimahi Creative MSMEs Thematic Community Service Program (Kuliah Kerja Nyata Tematik (KKN-T) UMKM Kreatif Cimahi) was implemented to empower local MSME entrepreneurs at the Milk Center of Cipageran Cimahi, which has strong potential yet continues to face challenges in financial record-keeping, packaging design, and the effective utilization of digital marketing. Through a participatory approach, Telkom University lecture and students implemented a series of programs including financial literacy workshop, product management and design workshop, digital marketing training, promotional content creation training, and digital mini showcase event. The results of the activities showed an increase in the knowledge and skills of MSMEs in business management, product design development, and digital-based marketing, so that this program contributed to encouraging the growth of MSMEs at Cipageran Milk Cente while strengthening the ecosystem of sustainable local economic empowerment in the digital era.